Recent advances in synthesis methods and surface structure manipulating strategies of copper selenide (CuSe) nanoparticles for photocatalytic environmental and energy applications - Chawla, Akshay; Sudhaik, Anita; Sonu; Kumar, Rohit; Raizada, Pankaj; Khan, Aftab Aslam Parwaz; Ahamad, Tansir; Nguyen, Van-Huy; Selvasembian, Rangabhashiyam; Kaushik, Ajeet; Singh, Pardeep (Journal of environmental chemical engineering, 2024)
The design and development of green and chemical nanomaterials is crucial because these systems can possess desired and manipulative photocatalysis and electrocatalysis. To achieve these features at the same time, Klockmannite Copper selenide (CuSe) emerging as a potential p-type semiconductor exhibits shape and size-dependent functional, optical, and electrical properties. Additionally, alterable bandgap, metallic character, localized surface plasmon resonance, and significant light absorption variability of CuSe make this class of material an efficient technological material. To cover the gaps in the field of CuSe and explore the potential to manage a sustainable environment, this review provides an overview of the design and development of green and chemical (but acceptable) CuSe for various advanced applications due to its indirect bandgap of 0.15–2.7 eV and scaled up synthesis using both top-down and bottom-up approaches. Despite numerous advantages, the limitations related to CuSe such as a small bandgap, charge carrier recombination, and a restricted ability to absorb visible light are also discussed in this article. Further, various modification possibilities, including doping or creating heterojunctions utilizing traditional (Type-I, -II, -III) and conventional techniques (Z-, Dual-Z-, S-scheme, etc.) to overcome these restrictions are also discussed carefully and critically. Functions of CuSe in energy conversion, supercapacitors, sensors, and environmental issue solutions have been covered in this study. Future outlooks, viewpoints, and conclusions on the subject have all been presented. We believe that this article will serve as a key document to project and promote CuSe for next-generation photocatalysis. [Display omitted] •Explored state-of-the-art CuSe photocatalyst developed using various synthesis strategies.•Novel modification strategies for CuSe involved in opto-electrochemical, charge transfer, and heterojunction formation.•Exploring Advanced Charge Transfer Techniques for In-Depth Understanding.•Emerging significant role of CuSe's in environmental remediation, energy conversion, and supercapacitors.•Discussed characterization challenges and techniques for CuSe photocatalytic potential demands.